Ilmu dan Agama dalam Perspektif Filsafat Ilmu - Muhammad Afton Rosyidi; M. Yunus Abu Bakar; Muhammad Nasrul Waton (Kartika: Jurnal Studi Keislaman, 2026)
Science and religion, within the perspective of philosophy of science, are closely interconnected, where science not only deals with empirical facts but also touches upon dimensions of value, ethics, and the meaning of life domains that belong to religion. Conversely, religion continues to interact with technological developments in understanding reality. This study examines the relationship between the two through a philosophical approach by exploring their ontological, epistemological, and axiological aspects, employing a descriptive-analytical method to analyze the views of Karl Popper, Thomas Kuhn, Stephen Jay Gould, and Alvin Plantinga. The findings indicate that science and religion are not mutually negating domains; rather, they can be positioned in a dialogical and integrative relationship. Ontologically, both are grounded in the same reality but from different perspectives; epistemologically, they possess distinct yet complementary validation methods; and axiologically, science provides a rational-empirical framework while religion offers value orientation, meaning, and ultimate purpose. This integration implies the importance of curricula and research that are not value-free but value-bound, ensuring that technological progress remains within ethical-spiritual corridors. The novelty of this research lies in synthesizing the thoughts of modern Western philosophers of science with the axiological dimension of religion, creating an integrative model relevant for civilization development in the era of technological disruption, transcending the mere theoretical debate between science and faith